Principles of Humanism in “A Critique of the Dialectical Reason” by Jean-Paul Sartre - Morkūnienė, Jūratė (Problemos, 1976)
An attempt is made in the article to interpret the problems of humanism in “A Critique of the Dialectical Reason” by J. P. Sartre. Certain evolution in his concept of humanism is noted. The main principles of Sartrean humanism change depending on the changes in his views on dialectics. In the work under consideration dialectics is no more regarded as a phenomenon of human consciousness only, but is considered in connection with experience. The principles of humanism, therefore, are based not on absolute freedom but on the possibility of free experience. In view of the prevailing ontological dualism, the concept of experience shows the idealistic conception of Sartre's humanism. The author concludes that in his “A Critique of the Dialectical Reason” Sartre does not give any new solution of the problem of humanism. The characteristics of humanism given by him remain abstract and subjectivistic.